The Cholinergic System and Inflammation: Common Pathways in Delirium Pathophysiology - Cerejeira, J (2012)
OBJECTIVES: To investigate whether delirium is associated with an unbalanced inflammatory response or a dysfunctional interaction between the cholinergic and immune systems. DESIGN: Cohort observational study. SETTING: General hospital orthopedic ward. PARTICIPANTS: One hundred one individuals aged 60 and older with no previous cognitive impairment undergoing elective arthroplasty. MEASUREMENTS: Incidence of postoperative delirium, plasma cholinesterase activity (acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE)) and inflammatory mediators (C-reactive protein (CRP), interleukin (IL)-1 beta, tumor necrosis factor alpha, IL-6, IL-8, IL-10) before and after surgery. RESULTS: Thirty-seven participants developed postoperative delirium and had greater production of CRP and proinflammatory to anti-inflammatory ratio after surgery. In participants with delirium, but not in controls, preoperative levels of plasma cholinesterase activity correlated with ΔCRP (AChE: ρ = 0.428, P = .008 and BuChE: ρ = 0.423, P = .009), ΔIL-6 (AChE: ρ = 0.339, P = .04), and ΔP/A ratio (AChE: ρ = 0.346, P = .04). CONCLUSION: Delirium was associated not only with an unbalanced inflammatory response, but also with a dysfunctional interaction between the cholinergic and immune systems. Comprehensive understanding of the relationship between the cholinergic and immune systems is crucial to developing new insights into delirium pathophysiology and novel therapeutic interventions